STRUCTURE OF SPACE, PERSONNEL AND EQUIPMENT OF HOSPITAL EMERGENCY DEPARTMENT OF BABOL UNIVERSITY OF MEDICAL SCIENCES BASED ON NATIONAL STANDARDS (2007) - MA Jahani (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Emergency care unit in the hospital should be able to save people’s lives when they are in danger and offer the emergency medical services. Factors such as personnel, space, and equipment can indicate the rate of preparedness and efficiency of emergency department and these criteria can be applied to compare the hospitals. The objective of this research was to study the structure of personnel, space and equipment in emergency care units of Babol University of medical sciences, Babol, Iran based on national standards in 2007.METHODS: This cross sectional study was performed on technical directors of emergency department, hospital administer, chief nurses, head nurses and supervisors of the hospitals of Babol medical University. The data gathered by questionnaire FINDINGS: Average number of servants and nursing assistants was 1 person and less than 1 person in each work shift. The average of space for each bed in emergency ward was 50 m2. There was a severe lack of space for emergency ward in Amirkola hospital. According to investing medical equipment, some items were less than standard limited and some were higher. In accordance with consuming medical equipment, there was not a difference between them and national standards.CONCLUSION: The results showed that the number of low level personnel needs to be increased and the courses related to management of emergency and triage for higher level personnel is required. In investing equipment part, it seems that some equipment should be repaired and replaced.